IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENERIMA POTONGAN UKT BAGI MAHASISWA YANG TERDAMPAK PANDEMI COVID-19 MENGGUNAKAN METODE TOPSIS - Winny Purbaratri; Roy Mubarak (IIB Darmajaya, 2021)
The Covid-19 pandemic has caused many new problems, including the community's economy, which has a major influence on the economy in the field of education. For students who are still financed by their parents, many end up not paying the Single Tuition Fee due to the condition of their parents who are not working or have their salaries cut during the Covid-19 pandemic. Decision Support System for Determining UKT Deduction Recipients for Students Affected by the Covid-19 Pandemic Using the Topsis Method. Can be a solution for universities to determine recipients of rocks from the Ministry of Education and Culture. Methodology This research was conducted with a 2-method approach, namely field studies conducted by interviewing the student affairs department who administers UKT assistance programs at universities and library studies to collect information related to decision support systems using the TOPSIS method. The results of the study in the form of a Decision Support System application using the Topsis Method helped accelerate the Higher Education Party to get a list of names of students who would receive UKT assistance. This web-based system is built with the PHP 7.4 programming language with the Bootstrap framework and MySQL database.